Wavelength dependent luminescence decay kinetics in `quantum-confined' g-C(3)N(4)nanosheets exhibiting high photocatalytic efficiency upon plasmonic coupling - Mondal, Sanjit; Sahoo, Lipipuspa; Vaishnav, Yuvraj; Mishra, Samita; Roy, Raj Sekhar; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Journal of Materials Chemistry A, 2020)
Serendipitous observations offer newer insights into materials properties. Here we describe g-C(3)N(4)nanosheets exhibiting remarkably blue-shifted photoluminescence within the 390-580 nm range centred at 425 nm which matches more closely with its `quantum-dots', and yet is excitation-wavelength independent. Moreover, surprisingly, the luminescence decay becomes increasingly slow at higher emission wavelengths, by up to 10 times. The nanosheets absorb only a fraction of visible-light. To improve this, when we designed a nanocomposite of g-C(3)N(4)and Au nanoparticles (NPs), it retained the PL characteristics and also exhibited excellent light-harvesting and photocatalytic efficiency for benzylamine (BA) oxidation. The surface plasmon resonance of the Au NPs is responsible for the high visible-light response and assisting the reaction by the `hot-electron' injection mechanism, while an uncharacteristic, pronounced co-catalytic effect by them further improves the efficiency. The conversion is 98% with >99% selectivity over 1.5 h of natural sunlight and open-air, probably the highest efficiency for BA photo-oxidation reactions. Even though such a dual role by plasmonic NPs has remained unscrutinized, we argue that the charge-transfer processes for the `hot-carrier' injection and co-catalytic events are well-separated in time due to a much slower photon incident frequency on a catalyst particle, enabling both to occur simultaneously in the same particle.

Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting